POSSIBILITIES OF TEACHER'S FORMATION IN THE PARFOR PROGRAM: ACHIEVEMENTS AND CHALLENGES - Martins, Adriana dos Reis [UNESP]; Andrade, Karylleila dos Santos; Bodnar, Roseli (Fundacao Univ Tocantins, 2018)
This paper presents a reflection on the Teaching of Arts in accordance with the Law of Directives and Bases of National Education of 1996. We sought to think about the professional responsible for this teaching, and on how the Legislation provides his/her formation. Lastly, we went to the state of Tocantins, which became the source of analysis of the public policies elaborated for the creation of the Art course in the language of drama - PARFOR program modality, at Federal University of Tocantins (Universidade Federal do Tocantins, UFT). -From a bibliographical and documentary research, we sought to understand the relationship between theory and practice in the formation of Art and Drama teacher and the influence of these experiences on the educational and interdisciplinary act of this professional in his/ her pedagogical actions. The considerations presented allowed us to conclude that thinking about our practices implies a continuous and developing work that can influence the pedagogical doing of the teacher in classroom activities.
Keywords: Arts; Drama; PARFOR; Federal University of Tocantins - UFT